Effect of boron carbide nanoparticles on the thermal stability of carbon/phenolic composites. Issue 9 (13th August 2015) - Rallini, Marco; Torre, Luigi; Kenny, Josè M.; Natali, Maurizio
Abstract : In this work, the use of nano‐boron carbide as a nanomodifier of phenolic matrix was envisioned. Particularly, nano‐boron carbide/phenolic‐based nanocomposites were produced and investigated. The obtained nanostructured matrices were also used to produce carbon fiber‐based bulk molding compounds (BMC). The thermal stability of nanocomposites and BMCs was investigated by thermogravimetric analysis both in nitrogen and in air atmospheres. The good dispersion and distribution of the nanosized particles in the matrix was confirmed by transmission electron microscopy while the post‐burning appearance of the BMCs was investigated by visual inspection and scanning electron microscopy. The experimental data highlighted the remarkable effects of nano‐boron carbide on the thermal stability and oxidation resistance of the carbon fiber‐based BMCs. Moreover, the boron oxide produced by the conversion of boron carbide allowed a substantial improvement of the dimensional stability of the BMC which also exhibited considerable residual structural integrity after burning. POLYM. COMPOS., 38:1819–1827, 2017. © 2015 Society of Plastics Engineers